Pelatihan Analisis Regresi Linier Sederhana Berbasis SPSS Bagi Guru SMP Swasta Di Jatinegara, Jakarta Timur - Erlando Doni Sirait; Dwi Dani Apriyani; Fajar Erlangga (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Improving the quality of education is strongly influenced by teacher’s competence, including the ability to write scientific papers based on research. However, many teachers face challenges in analyzing quantitative data due to limited knowledge of statistical tools such as SPSS. To address this issue, this Community Service Program (PkM) aimed to strengthen teachers' capacity in conducting data analysis using SPSS, with a focus on simple linear regression techniques. The activity took place at a private Junior High School in Jatinegara, East Jakarta, applying a participatory action research approach. The program included socialization, technical training, mentoring, and evaluation. The results indicated an increase in teachers’ understanding of identifying variables, entering data, and analyzing and interpreting regression results. Teachers also showed strong motivation in developing research ideas and writing scientific papers systematically. This activity not only improved their technical data analysis skills but also encouraged greater participation in scientific publication. The program contributes positively to teacher professionalism and holds potential for replication in other schools.